Differentiated approach to irrigation and elimination therapy - G. D. Tarasova (Медицинский совет, 2015)
Adequate performance of protective and other mechanisms of the nasal cavity is only possible in a reasonably clean environment, especially air. Deviation from the normal level of air content normally disturbs the functioning of the nasal cavity as organ. Long-term exposure to pathological components of air leads to organic disorders, in particular, to inflammatory diseases of the upper respiratory tract. These disorders which include infectious rhinitis, rhinosinusitis, adenoiditis, and allergic rhinitis (AR), not only worsen the quality of life of patients, but often require surgical intervention for the purpose of treatment or preventing complications. [1, 2, 4, 5, 31, 33]